Genomic surveillance of avian-origin influenza A viruses causing human disease - Lam, T; Pybus, O (BioMed Central, 2018)
Avian influenza A viruses (AIVs) pose a threat to global health because of their sporadic zoonotic transmission and potential to cause pandemics. Genomic surveillance of AIVs has become a powerful, cost-effective approach for studying virus transmission, evolution, and dissemination, and has the potential to inform outbreak control efforts and policies.